Benign Osseous Metaplasia of the Breast: A Rare Breast Lesion—Case Report With Clinicopathologic Features and Review of the Literature - Mukund Tinguria; Angela Fleming (Case Reports in Pathology)
Benign osseous metaplasia of the breast is an extremely rare breast lesion. This is a report of a 79-year-old woman who presented with a right breast lesion. The lesion was found incidentally on computed tomography (CT) scan examination of the chest. Subsequent mammogram showed coarse calcification within a round circular area measuring approximately 12 mm in size. Ultrasound examination showed an ill-defined 9×9×9 mm hypoechoic lesion with calcification and internal vascularity. Histologic examination of the excised lesion showed features of benign osseous metaplasia. There was no evidence of atypia and malignancy. The subsequent immunohistochemistry confirmed the diagnosis. The immunohistochemical staining for epithelial markers—pancytokeratin (AE1/AE3), Cam 5.2, HMWCK (34Be12), and CK5—was negative in the stromal component, which ruled out a metaplastic carcinoma. Osseous metaplasia occurs in association with a wide variety of benign and malignant breast lesions. However, primary benign osseous metaplasia in the absence of breast disease is an extremely rare entity. The case presented here is a reminder that osseous metaplasia can occur in the breast in isolation. The case also emphasizes the value of thorough histopathological examination in making the diagnosis, as clinical and imaging studies cannot differentiate between neoplastic and non-neoplastic lesions as well as benign and malignant neoplasms with certainty.